Identification of resistance germplasm in sesame against root and stem rot (Macrophomina phaseolina) of Sesame: Identification of resistance germplasm in sesame against root and stem rot (Macrophomina phaseolina) of Sesame - K N GUPTA; SHIVANI NAGPURE; RAJNI BISEN (Journal of Oilseeds Research, 2023)
3700 accessions of sesame germplasm were sown during kharif 2021 with susceptible and resistant checks in augmented plot design in 3 meter length row in sick plot (artificial inoculum) condition. Out of these accessions, only 53 accessions were resistant against root and stem rot of sesame and disease incidence was less than 10%.